Multistep molecular mechanism of amyloid-like aggregation of nucleic acid-binding domain of TDP-43 - Pillai, Meenakshi; Jha, Santosh Kumar (Proteins- Structure Function and Bioinformatics, 2023)
TDP-43 protein is associated with many neurodegenerative diseases and has been shown to adopt various oligomeric and fibrillar states. However, a detailed kinetic understanding of the structural transformation of the native form of the protein to the fibrillar state is missing. In this study, we delineate the temporal sequence of structural events during the amyloid-like assembly of the functional nucleic acid-binding domain of TDP-43. We kinetically mapped the aggregation process using multiple probes such as tryptophan and thioflavin T (ThT) fluorescence, circular dichroism (CD), and dynamic light scattering (DLS) targeting different structural events. Our data reveal that aggregation occurs in four distinct steps-very fast, fast, slow, and very slow. The ``very fast'' change results in partially unfolded forms that undergo conformational conversion, oligomerization and bind to ThT in the ``fast step'' to form higher order intermediates (HOI). The temporal sequence of the formation of ThT binding sites and conformational conversion depends upon the protein concentration. The HOI further undergoes structural rearrangement to form protofibrils in the ``slow'' step, which, consequently, assembles in the ``very slow'' step to form an amyloid-like assembly. The spectroscopic properties of the amyloid-like assembly across the protein concentration remain similar. Additionally, we observe no lag phase across protein concentration for all the probes studied, suggesting that the aggregation process follows a linear polymerization reaction. Overall, our study demonstrates that the amyloid-like assembly forms in multiple steps, which is also supported by the temperature dependence of the kinetics.
Keywords: aggregation pathway; amyloid-like assembly; conformational conversion; kinetics; oligomers